Community-Based Kambo Tourism Area Planning With a Participatory Planning Approach - Amiruddin Akbar Fisu; Zulham A. Hafid; Liza Utami Marzaman; Didiharyono D.; Ulfa Utami Mappe; Abri Hadi; Suparman Manuhung (Universitas Andi Djemma, 2023)
At the end of 2021 Kambo was selected as the Top 100 Indonesian Tourism Village Award (ADWI) 2021 by the Ministry of Tourism and Creative Economy. This proves that Kambo has huge tourism potential. However, this potential has not been managed properly. This can be seen from the absence of management and governance of tourism activities carried out by the local community. Kambo also does not have planning documents related to tourism development, either in the form of an academic manuscript or a master plan. Even the things discussed and determined at the sub-district level musrembang have not accommodated these, while in fact, these documents are very important to be a guideline for planning and developing tourism. For this reason, the Palopo Urban Forum with Andi Djemma University took the initiative together with a number of volunteers from various communities, institutions and professions, taking a role to participate in assisting the residents of Kambo in identifying problems, mapping potential and designing places, through the Placemaking Workshop. The Placemaking Workshop is broadly a tourism planning with a participatory approach so as to provide space and opportunity for the people of Kambo to tell stories about their village, knitting history, describing the area, explaining existing problems, expressing hopes and aspirations, and making concepts and plans together. The people of Kambo are the holders of the right to the future of their own territory. Therefore, they are really in charge of the vision, planning, activities and efforts to control their own living space.